(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background : Diabetes mellitus is a metabolic disorder of multiple aetiologies characterized by chronic hyperglycemia resulting from defects in insulin secretion or insulin action. Muscle strength is influenced by insulin resistance, through higher plasma levels, and lipid content in the muscle, therefore it could be a marker for impaired skeletal muscle. These structural and functional changes in the skeletal muscle caused by defective insulin action could be associated with muscle weakness and reduced endurance capacity. This study evaluates the subclinical changes in muscle strength in diabetes and its functional performance comparing with age-matched healthy subjects. Methods: This observational study totally includes 80 male and female individuals, 40 of type 2 DM and another 40 of age matched healthy individuals without any difficulty in Activities of daily living were recruited above 60 years of age, and assessed with HHD and functional measure (FTSTS) and quality of life measure (SF 36) used. Results: Independent sample T test and Pearson correlation coefficient was used to analyze the difference and correlate among lower extremity muscle strength, FTSTS, and SF 36 in diabetic and healthy individuals; the data obtained were statistically significant, except SF 36 emotional limitation and physical limitation factor were non-significant. Pearson’s coefficient found to have weak negative correlation in SF 36 and muscle strength. Conclusion: Type 2 diabetes mellitus has correlated with reduction in muscle strength particularly in lower limb which remains subtle and unidentified as the disease progresses the muscle weakness may become progressive and lead to immobilit